Partnerstwo i konkurencyjność w świetle polityki spójności Unii Europejskiej - Bembenek, Bogusław (Partnership and Competitiveness in the Light of Cohesion Policy, 2006)
The article presents general problems regarding cohesion policy in the EU. The importance of partnership in the execution of this policy has been presented. The author believes that partnership understood in a wide aspect directly influences competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 106-117